SYNTHESIS AND CHARACTERIZATION OF COPPER-SELENIO TYPE NANOSTRUCTURES OBTAINED THROUGH MICROWAVE AND MECHANOSYNTHESIS TECHNIQUES - Guzmán Duxtan, Aldo Javier (2021)
In this work, the synthesis of copper selenide nanostructures is described, using the microwave and mechanosynthesis technique. In microwave-assisted synthesis, the process was carried out in a modified microwave oven. To this a solution of sodium sulfite was added with selenium powder, this mixture was subjected to microwave radiation at 40 %, thus forming sodium selenosulphate for then add copper acetate maintaining the Cu: Se ratio (1: 1) while undergoing irradiation again, obtaining at the end a black precipitate of copper selenide. The other technique is mecanosynthesis, where copper and selenium powders were ground under inert atmosphere, using a SPEX 8000M mill, obtaining copper selenide. The products were characterized by DR-X, FRX-ED, MEB, EDX, UV-Vis. The results indicate that the Cu2Se, Cu3Se2 and Cu1.8Se phases were formed. Using the equations of Scherrer and Williamson-Hall, the average diameter of the crystallite was determined between 8 and 83 nm, and with the help of the OriginPro 2017 program, microtensions that were between 0.00105 to 0.01031 Pa were calculated. The banned energy band was obtained using the plot of Tauc, obtaining values between 1 and 2 eV.